2011
DOI: 10.1002/crat.201000634
|View full text |Cite
|
Sign up to set email alerts
|

Seed loading effects on the mean crystal size of acetylsalicylic acid in a continuous‐flow crystallization device

Abstract: This study investigates the effects of seed loading on the mean crystal size of the model substance, acetylsalicylic acid, crystallized from ethanol in a continuously seeded tubular crystallizer. A hot, highly concentrated ethanolic acetylsalicylic acid solution was mixed with an acetylsalicylic acid-ethanol seed suspension. Subsequent cooling of the slurry in the tubing promoted supersaturation and hence crystal growth. The tubular shape of the 15 m-long crystallizer with an inner diameter of 2 mm enabled nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 49 publications
(71 reference statements)
3
96
0
Order By: Relevance
“…The particle size distribution (PSD) of the produced crystals affects downstream processes such as filtration, milling, and formulation [1,5]. Furthermore, the solubility, disintegration, and dissolution rate of medicines in the human body depend on this parameter [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particle size distribution (PSD) of the produced crystals affects downstream processes such as filtration, milling, and formulation [1,5]. Furthermore, the solubility, disintegration, and dissolution rate of medicines in the human body depend on this parameter [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Particle size control is extremely important during crystallization processes in the chemical and pharmaceutical industry [1][2][3][4]. The particle size distribution (PSD) of the produced crystals affects downstream processes such as filtration, milling, and formulation [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Continuously seeded cooling crystallization can suppress undesired nucleation events or the formation of crystals of an undesired morphology. Thus, a stable steadystate operation is feasible and scaling/clogging issues can be reduced [49,92,103]. The current work focuses on the development of a device for continuous seed crystal generation by abrasion from larger parent or product crystals, followed by a mechanical classification of the desired crystal fraction.…”
Section: Coiled Flow Inverter For Crystallizationmentioning
confidence: 99%
“…For example, Lawton et al 17 reported the application of a continuous oscillatory 5 baffled crystallizer (COBC) for a cooling crystallization which offered significant advantages in operating cost and processing time. Eder [18][19] and his colleagues investigated the impacts of flow rate and seed loading in continuously-seeded tubular cooling crystallizers for the production of active pharmaceutical ingredients (APIs). Ferguson et al 20 reported the employment of a variety of process analytical technology (PAT) tools for particle size and solute concentration measurement in a plug flow crystallizer.…”
Section: Introductionmentioning
confidence: 99%